(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Polyvinylidene fluoride (PVDF) has excellent mechanical, electrical, and thermal properties, making it suitable for a wide range of industrial and technological applications. PVDF-filled epoxy composites were prepared at 1% to 10% loadings via the casting method to improve the mechanical and thermal properties of epoxy. Tensile strength, tensile modulus, flexural strength, and flexural modulus are the lowest at 1% PVDF filler due to insufficient reinforcement by low filler loading. Besides, the presence of high void content resulting in a drop of tensile strength and flexural strength to lower than the epoxy alone. Strength and modulus increased at 3% and 5% loading, then decline again at much higher loadings. At high loading of PVDF, the strength and modulus are reduced due to the filler agglomerations which are supported by the density and percentage of void content. Besides causing voids inside the composites system, filler agglomerations also act as stress concentration sites.